Effect of tanniniferous Acacia karroo leaf meal inclusion level on feed intake, digestibility and live weight gain of goats fed a Setaria verticillata grass hay-based diet - Brown, David; Ng’ambi, Jones W.; Norris, David (Journal of Applied Animal Research, 2017)
This study aimed to investigate the effects of tanniniferous Acacia karroo leaf meal inclusion level on performance of goats fed on a Setaria verticillata grass hay-based diet. Twenty indigenous male Pedi goats with an average initial live weight of 17.44 ± 2 kg were allocated, in a completely randomized design, to five dietary treatments containing Acacia karroo leaf meal inclusion levels of 20%, 25%, 30%, 40% and 50% of the total diet. Daily dry matter intakes were similar (P > .05) across the treatments. Acacia karroo leaf meal inclusion improved (P < .05) dry matter, organic matter, crude protein, neutral detergent fibre and acid detergent fibre digestibility coefficients. Dietary treatments had no effect on final live weights of goats. However, live weight gains were higher (P < .05) in goats fed a diet containing 50% Acacia karroo leaf meal inclusion level. Dry matter, crude protein and neutral detergent fibre digestibility coefficients were optimized at Acacia karroo leaf meal inclusion levels of 69.4%, 48.3% and 42.7%, respectively. Acacia karroo leaf meal inclusion improved nutrient digestibility and live weight gain of the goats and thus has potential to be utilized as a protein supplement when low-quality roughage is used as a basal diet.
Journal article published in Journal of Applied Animal Research, 2018 VOL. 46, NO. 1, 248–253
Keywords: Acacia karroo; Goat; Tannis; Inclusion; Goats; Acacia; Animal feeds; Feeds-- Weight and measurement